A Human Rights’ Tale of Competing Narratives / Um Relato de Narrativas Rivais de Direitos Humanos - Sandoval, Carlos Arturo Villagrán; Veçoso, Fabia Fernandes Carvalho (Revista Direito e Práxis, 2017)
DOI: 10.12957/dep.2017.28035 Abstract The paper explores the 2016 financial crisis experienced by the Inter-American Commission on Human Rights as an illustrative example within a larger context for rethinking the Inter-American System of Human Rights. We argue that reform must involve a reexamination of the dialectic roles of both member states and Inter-American institutions. The goal is to create new institutional opportunities that can cope with the current contexts of rights violations related to inequality, poverty and income distribution. It is also argued that different human rights narratives are at play within the context of the Inter-American System today, that is, the universalistic narrative of Ius Constitutionale Commune and the less explored story of member states resisting compliance with Inter-American decisions. These narratives are connected to the tension between the main goal of protecting human rights in the Americas and the member states’ roles as the System’s material supporters. The prevalence of the unidirectional and institutionalist narrative of Ius Constitutionale Commune may have contributed to the current challenges experienced within the Inter-American System. Member states have rebelled in recent times against this universal approach, particularly since the later years of the first decade of the 2000s. However, the Inter-American institutions continue to be nonresponsive to this backlash. This paper argues that rather than treating states as entities to be kept under strict surveillance and mistrust, the Inter-American System should be changed and reimagined through dialogue and a deeper consideration of domestic contexts, thus enabling its survival, and encouraging member states to participate at higher levels. Keywords: Inter-American System of Human Rights; financial crisis; Ius Costitutionale Commune; member states; reform. Resumo Este artigo analisa a crise financeira vivida pela Comissão Interamericana de Direitos Humanos em 2016 como exemplo de um contexto mais amplo relacionado à necessária reflexão sobre a reestruturação do Sistema Interamericano de Direitos Humanos. Argumenta-se que a reforma do sistema deve envolver o reexame dos papéis dialéticos tanto dos Estados-membros, quanto das instituições interamericanas. O objetivo maior desse esforço de reforma seria possibilitar a criação de oportunidades institucionais que pudessem dar conta dos contextos atuais de violação de direitos na região, relacionados à desigualdade, pobreza e redistribuição de renda. Argumenta-se também que diferentes narrativas de direitos humanos se articulam no contexto do Sistema Interamericano atualmente, quais sejam, a narrativa universalista do Ius Constitutionale Commune e a narrativa menos explorada relacionada à resistência dos Estados-membros em dar cumprimento às decisões interamericanas em âmbito doméstico. Essas duas narrativas estão conectadas à tensão existente entre o objetivo maior de proteção de direitos humanos nas Américas e o papel dos Estados-membros como sustentáculo material do Sistema Interamericano. A prevalência da narrativa unidirecional e institucionalista do Ius Constitutionale Commune pode ser vista como fator que tem contribuído para o incremento dos desafios experimentados pelo Sistema Interamericano atualmente. Estados-membros têm se rebelado contra essa abordagem universalista, particularmente desde as primeiras décadas dos anos 2000. No entanto, as instituições interamericanas continuam a ignorar tais reações estatais. Este artigo afirma que Estados não devem ser tratados como entidades que devam ser mantidas sob estrita vigilância, em um contexto de constante desconfiança. A reforma do Sistema Interamericano deve ocorrer por meio de diálogo e levando-se em consideração os diversos contextos domésticos, possibilitando assim a sobrevivência do sistema, além de encorajar uma participação mais intensa dos Estados-membros. Palavras-chave: Sistema Interamericano de Direitos Humanos; crise financeira; Ius Costitutionale Commune; Estados-membros; reforma.